2004
DOI: 10.1007/s10227-005-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Nonviral Uses of Imiquimod: A Review

Abstract: Imiquimod has been shown to be a safe and effective treatment for a variety of skin conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 94 publications
1
89
0
3
Order By: Relevance
“…These results are similar to those obtained with 3 applications/week (Edwards et al 1998;Garland et al 2001). Therefore, 3 times per week treatment schedule is recommended because of a relatively lower rate of side effects (Perry and Lamb 1999;Gupta et al 2004;Chang et al 2005;Scheinfeld and Lehman 2006).…”
Section: External Genital and Perianal Wartssupporting
confidence: 83%
“…These results are similar to those obtained with 3 applications/week (Edwards et al 1998;Garland et al 2001). Therefore, 3 times per week treatment schedule is recommended because of a relatively lower rate of side effects (Perry and Lamb 1999;Gupta et al 2004;Chang et al 2005;Scheinfeld and Lehman 2006).…”
Section: External Genital and Perianal Wartssupporting
confidence: 83%
“…Furthermore, Wang et al (43) investigated the action of a dual TLR7/8 agonist in tumor-bearing mice, and demonstrated that subcutaneous administration of the above TLR7/8 agonist effectively prevented lung metastasis by inducing Th1-type immune responses and potent antitumor activity in mice via TLR7 and MyD88-dependent pathways (43). In addition, the TLR7 agonist imiquimod has been successfully applied in the treatment of actinic keratosis, basal cell carcinoma, Bowen's disease and lentigo maligna (44,45).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported high efficacy of imiqimod for the treatment of superficial BCC with a cure rate ranging from 43-94% (42-45), whereas it is less efficacious for nodular BCC with a cure rates of 50-65% (43,46). Imiquimod has also been used in the treatment of warts, actinic keratosis, Bowen's disease and lentigo maligna melanoma (17,18). In addition to imiquimod, other topical agents, such as nicotinamide, all-trans retinoic acid, adapalene, zinc and sodium tosylchloramide have also been reported to act through TLRs (47).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their role in tumor development and progression has attracted increasing attention recently (11). Imiquimod, an agonist of TLR7 (16) has been shown to induce the expression of several cytokines such as IFN-α, IL-12 and TNF-α, which mediate its anticancer effects (pro-apoptotic, anti-invasive and anti-angiogenic) (17). It may be applied topically in the treatment of premalignant and malignant skin disorders, in particular BCC (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation